6
$\begingroup$

I obtained the following Fibonacci identities experimentally using SageMath code. Can these be proved theoretically?

Identity 1: $$ \sum_{n = 0}^{\infty} \frac{F_{n}x^{n}}{n!} + e^x\sum_{n = 0}^{\infty} \frac{F_{n}(-x)^{n}}{n!} = 0 $$

Identity 2:

$$ 52\sum_{n = 0}^{\infty} \frac{F_{4n}x^{4n}}{4n!} = 156 \sum_{n = 0}^{\infty} \frac{F_{4n+1}x^{4n+1}}{(4n+1)!} = 585 \sum_{n = 0}^{\infty} \frac{F_{4n+2}x^{4n+2}}{(4n+2)!} = 630 \sum_{n = 0}^{\infty} \frac{F_{4n+3}x^{4n+3}}{(4n+3)!} $$

$\endgroup$
14
$\begingroup$

Using Binet's formula we have

$$\sum_{n}\frac{F_nx^n}{n!} =\frac1{\sqrt5}\left(\sum_n\frac{(\phi x)^n}{n!} -\sum_n\frac{(-\phi^{-1} x)^n}{n!}\right) =\frac1{\sqrt5}(e^{\phi x}-e^{-\phi^{-1}x})$$

while,

$$e^x\sum_{n}\frac{F_n(-x)^n}{n!} =\frac{e^x}{\sqrt5}\left(\sum_n\frac{(-\phi x)^n}{n!} -\sum_n\frac{(\phi^{-1} x)^n}{n!}\right) =\frac1{\sqrt5}(e^{(1-\phi) x}-e^{(1+\phi^{-1})x})$$

and the first identity is consequence of the equality $1-\phi=-\phi^{-1}$.

EDIT: I've just checked numerically the second identity, and apparently it is false. The original question included a snippet of SAGE code, and I think the problem was that $4r$ is interpreted as $4$ by SAGE.

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

Identity 1: Note by the power series product formula this identity $$ \sum_{n = 0}^{\infty} \frac{F_{n}x^{n}}{n!} + e^x\sum_{n = 0}^{\infty} \frac{F_{n}(-x)^{n}}{n!} = 0 $$ can be written

$$\sum_{n = 0}^{\infty} \frac{F_{n}x^{n}}{n!} + \sum_{n = 0}^{\infty}\left(\sum_{k=0}^n\binom{n}{k}\frac{F_{k}(-1)^{k}}{k!}\frac{1}{(n-k)!}\right)x^n = 0$$

So you'd need to show for all $n$ $$ \frac{F_{n}}{n!}=\sum_{k=0}^n\binom{n}{k}\frac{F_{k}(-1)^{k+1}}{n!} $$ which simplifies

$$ F_{n}=\sum_{k=0}^n\binom{n}{k}F_{k}(-1)^{k+1} $$

Unfortunately I was unable to prove this without Binet's Formula: $F_k=\dfrac{\varphi^k-\varphi^{-k}}{\varphi-\varphi^{-1}}$ . So it's really a worse version of iqcd's proof but here it is anyway.

$$ \begin{align} \sum_{k=0}^n\binom{n}{k}F_{k}(-1)^{k+1} &=\sum_{k=0}^n\binom{n}{k}(-1)^{k+1}\frac{\varphi^k-\varphi^{-k}}{\varphi-\varphi^{-1}}\\ &=\frac{1}{\varphi-\varphi^{-1}}\sum_{k=0}^n\binom{n}{k}(-1)^{k+1}\varphi^k-\sum_{k=0}^n\binom{n}{k}(-1)^{k+1}\varphi^{-k}\\ &=\frac{1}{\varphi-\varphi^{-1}}\sum_{k=0}^n\binom{n}{k}(-\varphi^{-1})^k-\sum_{k=0}^n\binom{n}{k}(-\varphi)^{k}\\ &= \frac{1}{\varphi-\varphi^{-1}}[(1-\varphi^{-1})^n-(1-\varphi)^n]\\ &= \frac{1}{\varphi-\varphi^{-1}}[(\varphi)^n-(\varphi^{-1})^n]\\ &= F_n \end{align} $$

That second to last line is because for the golden ratio $\varphi$, we have $1-\varphi=\varphi^{-1}$ similarly $1-\varphi^{-1}=\varphi$.

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

According to this paper:

$\sum_{n = 0}^{\infty} \frac{F_{n}x^{n}}{n!}= \frac{e^{\alpha x}-e^{\beta x}}{\alpha - \beta}$ where $\alpha$ and $\beta$ are roots of the Fibnocci polynomial $x^2-x-1$.

This makes the first identity equivalent to $G(x) = G(-x)e^{x}$ where $G(x) = \frac{e^{\alpha x}-e^{\beta x}}{\alpha - \beta}$. And that, in turn, is equivalent to $1-\alpha=\beta$ and $1-\beta =\alpha$, which are both equivalent to $\alpha+\beta =1$, which follows from the fact that the sum of roots of a quadratic polynomial add up to the coefficient of $x$ times negative one.

Note that the search term to use is "exponential Fibonocci generating function".

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.